A Nudging Approach to Promote Healthier and More Sustainable Food Consumption and Lifestyles at the University of Milano-Bicocca - Matteo Colleoni; Massimiliano Rossetti; Giacomo Magatti; Paola Palestini; Giovanna Iannantuoni (Journal of Sustainability Perspectives, 2021)
Since it was founded in 1998, the University of Milano-Bicocca has worked to make its structures environmentally, socially, and economically sustainable, not only to reduce the costs and environmental impact of its management processes, but also to promote sustainable behaviour on the part of its employees, lecturers and students. This report focuses on the measures implemented by the university in order to make food consumption and lifestyles healthier and more sustainable. Inspired by nudge theory (according to which in order to achieve a change in behaviour it is necessary to act on indirect encouragement and enablement rather than on direct instruction, enforcement and punishment), these measures aimed to promote healthier and more appropriate styles of food consumption, in particular at university canteens. The interventions were oriented both towards offering healthier products and towards modifying the environment in order to encourage more balanced food choices. The programme of interventions was divided into three phases: firstly an investigation of eating behaviours and lifestyles; secondly planning the interventions; and finally evaluating the project and disseminating good practices